Exploring the relationship between mentoring and doctors' health and wellbeing: a narrative review. (May 2017) - Wilson, Gemma; Larkin, Valerie; Redfern, Nancy; Stewart, Jane; Steven, Alison
The health and wellbeing of doctors are crucial, both for the individuals themselves and their ability to deliver optimum patient care. With increased pressures on healthcare, support mechanisms that attend to doctors' health and wellbeing may require greater emphasis to safeguard those working in frontline services. To inform future developments, this systematic narrative review aimed to identify, explore and map empirical and anecdotal evidence indicating the relationships between mentoring activities and the health and wellbeing of doctors. Twelve databases were searched for publications printed between January 2006 and January 2016. Articles were included if they involved doctors' engagement in mentoring activities and, either health or wellbeing, or the benefits, barriers or impact of mentoring. The initial search returned 4669 papers, after exclusions a full-text analysis of 37 papers was conducted. Reference lists and citations of each retrieved paper were also searched. Thirteen papers were accepted for review. The Business in the Community model was used as a theoretical framework for analysis. Mentoring influenced collegiate relationships, networking and aspects of personal wellbeing, such as confidence and stress management, and was valued by doctors as a specialist support mechanism. This review contributes to the evidence base concerning mentoring and doctors' health and wellbeing. However, it highlights that focused research is required to explore the relationship between mentoring, and health and wellbeing.